Modélisation de l'impact de l'initiative TSA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
En juin 2003, l'IRIDEM a publié un document de travail sur 'l'initiative...